Servitization across countries and sectors: Evidence from world input-output data - Klaus S. Friesenbichler; Agnes Kügler (Austrian Institute of Economic Research (WIFO), 2021)
We use the supply tables that underlie WIOT data to explore the provision of services by manufacturing sectors. The value-added shares generated by services differ substantially across countries and sectors, while they remain largely stable over time. A Bayesian classification assigns broadly defined manufacturing sectors to economy-wide growth models. It differentiates between service- and manufacturing driven models in catching up and developed economies. Servitization increase with labour productivity. The service intensities in the sectoral production mix are lower in countries with higher manufacturing shares. This holds for both catching up and developed economies. However, servitization is largely unrelated to productivity and employment growth. Hence, we argue that the degree of servitization is contingent on and an attribute of the respective economic model in which a sector operates.
Keywords: L60; P51; O14; 330; servitiziation; employment; productivity; latent class analysis; WIOD